DIURETIC ACTIVITY OF MATOA LEAVES EXTRACTS (Pometiapinnata) AND ITS INFLUENCE ON POTASSIUM AND SODIUM LEVELS - Purwidyaningrum, Ika; Sukandar, Elin Yulinah; Fidrianny, Irda (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The purpose of this study was to determine diuretic activity of matoa leaves (Pometiapinnata) extracts and fraction and its influence on potassium and sodium levels. Methods: Matoa leaves were extracted by reflux method followed by evaporation using rotary evaporator. The subjects were male Wistar rats that were divided into 11 group furosemide (3.6 mg/kg bw), control group CMC 0.5%, matoa leaves extracts with doses of 50 mg/kg bw, 100 mg/kg bw, 150 mg/kg bw, matoa leaves aqueous fraction with dose of 10.94 mg/kg bw, 21.88 mg/kg bw, 32.82 mg/kg bw, matoa leaves ethyl acetate fraction with dose of 4.35 mg/kg bw, 8.71 mg/kg bw, 13.06 mg/kg bw. Rats were placed in metabolic cagesduring observation study. Urine volume was measured for 5 to 24 hours. Potassium and sodium levels in urine were determined by using Atomic Absorption Spectrophotometry. Results: The effective dose of matoa leaves extract and fractions for diuretic activity was matoaleaves ethyl acetate fraction 8.71 mg/kg bw which could increase the excretion of sodium and potassium in the urine of the male Wistar rats. Conclusion:Matoa leaves extract and fractions could increase the excretion of sodium and potassium in the urine of the male Wistar rats. Â  Â 